Anxiety level modulates endocrine and neuromodulatory responses to maximal exercise and 24-h recovery in elite rowers - Ostapiuk-Karolczuk, Joanna; Dziewiecka, Hanna; Kasperska, Anna; Cichoń-Woźniak, Justyna; Reysner, Małgorzata; Gruszka, Wojciech; Basta, Piotr; Kaczmarczyk, Sabina; Skarpańska-Stejnborn, Anna (Frontiers in Physiology, 2025)
IntroductionAnxiety is a key psychological factor in competitive sport that interacts with physiological stress responses. By modulating neuroendocrine and neurotransmitter activity, it may influence how athletes adapt to maximal effort and recover afterward. The study addressed the gap in understanding how pre-exercise anxiety affects the recovery dynamics of these responses in elite endurance athletes.Materials and methodsSixteen highly trained male rowers performed a standardized 2000-m maximal ergometer test and were classified into Low (n = 8) and High anxiety (n = 8) groups based on pre-exercise Sport Competition Anxiety Test (SCAT; low <25, high ≥25) scores using established interpretive guidelines. Venous blood was collected before, immediately after, 1 h, and 24 h post-exercise. Serum cortisol, testosterone, serotonin, dopamine, β-endorphin, anandamide (AEA), and 2-arachidonoylglycerol (2-AG) were analyzed. Testosterone-to-cortisol (T/C) and serotonin-to-dopamine (S/D) ratios were calculated as indices of anabolic-catabolic balance and serotonergic-dopaminergic regulation.ResultsCortisol increased post-exercise in both groups and remained elevated at 24 h, with prolonged elevation in the High anxiety group (+17.9% vs. +7.8%; p = 0.03). Testosterone peaked at 1 h, with a larger rise in the High anxiety group (+42.2% vs. +31.5%; p = 0.02). β-endorphin increased post-exercise in both groups (p < 0.01). Serotonin remained higher and dopamine recovered more slowly in the High anxiety group (p < 0.05). Performance time during the 2000-m test was comparable between groups.ConclusionAnxiety level measured before maximal rowing was associated with distinct endocrine and neuromodulatory response patterns, indicating greater internal load despite similar external performance. These findings may support individualized recovery strategies in high-performance sport. The sample size and elite-athlete characteristics may limit the broader applicability of the findings.